1995
DOI: 10.1159/000127024
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Endotoxin Treatment Decreases Immune and Hypothalamo-Pituitary-Adrenal Axis Responses: Effects of Orchidectomy and Testosterone Therapy

Abstract: It is known that in vivo administration of bacterial endotoxin activates immune cells to release cytokines, these substances in turn enhancing hypothalamo-pituitary-adrenal (HPA) axis function; additional evidence supports the existence of an immune-neuroendocrine sexual dimorphism. In the present study, we investigated: (1) the in vivo response of both the HPA and the immune systems to single and repeated endotoxin administrations in mice, and (2) whether testosterone possesses a modulatory effect on neuroend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
9
19
1
Order By: Relevance
“…We recently found that repeated injections of LPS in intact mice over a 5-days period induce tolerance of both the immune (TNF-α) and the neuroendocrine (corticotrope) axes [33, 34]. In the present study, corticotrope hyperresponsiveness appears in ADX + CB animals, whereas tolerance of TNF-α secretion to repeated LPS injections remains normal.…”
Section: Discussionsupporting
confidence: 54%
“…We recently found that repeated injections of LPS in intact mice over a 5-days period induce tolerance of both the immune (TNF-α) and the neuroendocrine (corticotrope) axes [33, 34]. In the present study, corticotrope hyperresponsiveness appears in ADX + CB animals, whereas tolerance of TNF-α secretion to repeated LPS injections remains normal.…”
Section: Discussionsupporting
confidence: 54%
“…The different adrenal response to acute or chronic LPS administration can be explained by a tolerance phenomenon. Different data have been reported depending on the times of administration and the doses used -from a lowered to an almost absent adrenal response to LPS (Mefford et al 1991, Mengozzi & Ghezzi 1991, Hadid et al 1995. The tolerance to chronic LPS administration seems to be related to decreased macrophage responsiveness to LPS, rather than to a decreased neuroendocrine response to cytokines (Mefford et al 1991, Hadid et al 1996.…”
Section: Discussionmentioning
confidence: 98%
“…64 Plasma IL-1 and TNF-a responses to repeated LPS injections were much smaller than those to acute LPS injection. 64,77 The decreased cytokine production may be due to an alteration in peripheral sympathetic tone, 79,80 but it remains unclear whether repeated LPS injection altered cytokine receptor or neuronal responses at the post-receptor level. A normal glucocorticoid response to endotoxemia seems to be necessary for the development of full tolerance of the HPA axis.…”
Section: Repeated Lps Administrationmentioning
confidence: 99%